A comparative review of Haute Autorité de Santé and National Institute for Health and Care Excellence health technology assessments of Ikervis® to treat severe keratitis in adult patients with dry eye disease which has not improved despite treatment with tear substitutes. Issue 1 (1st January 2017) - Eroglu, Yasmina Iffet
ABSTRACT: Background: In 2015, Ikervis® became the only EMA-approved cyclosporine A (CsA) eye-drop for the treatment of severe keratitis in adult patients with dry eye disease, which has not improved despite treatment with tear substitutes. Since the 1980s, CsA has been used empirically for ocular conditions in veterinary medicine then in humans. However, its extremely low aqueous solubility led to its administration in vegetable oils, which is characterized by low ocular availability, poor intraocular penetration, poor tolerability and short shelf-life. Concentrations from 0.05% to 2% are compounded on an industrial scale and reimbursed throughout Europe. In France, Ikervis® has been granted an ASMR score of 5 by HAS, whereas in UK NICE endorsed its use.Objective: To review the dry eye disease environment, its challenges and available treatment options, and compare the NICE and HAS assessments to question HAS' decision to maintain full reimbursement of compounded CsA formulations in the absence of evidence, while reimbursing the EMA-approved drug at 15%. Method: extensive search on PubMED.Results: Comparator selection, composite score assessment and use of CE model are key differentiators.Conclusion: In topical formulations, improvements to the vehicle are key innovations that can bring significant benefits. After the USA, a Compounding Act is needed in Europe.